Educating Family Physician Residents for Anesthetic Preoperative Evaluation and Clearance - Gerber, Benjamin; Roth, Eyan; Laubach, Tyler; De Jong, Luke; Kasper, Travis; Perry, Jarrett; Johnson, Allan; Krogman, William; Newton, Felecia; Powell, Sara; Bragg, Dee Ann; Regehr, Jared (Kansas Journal of Medicine, 2023)
Introduction. Encounters for preoperative clearance are common within primary care offices, so it is imperative that family medicine residents learn how to perform preoperative assessments. We assessed family medicine residents’ knowledge of preoperative evaluation and clearance in preparation for surgery by providing a pre- and post-test alongside a didactic seminar. Methods. A didactic seminar on preoperative evaluations was presented at a family medicine resident didactics session by two senior anesthesiology residents. A 16 question, multiple choice test was used as both a pre-test and post-test to assess family medicine residents’ knowledge. Results. A total of 31 participants took the pre-test (residents = 24; medical students = 7), and 30 participants took the post-test (residents = 23; medical students = 7). Mean scores and standard deviations were calculated for both tests with an average score of 37.50% ± 10.58% and 45.42% ± 11.12% on the pre- and post-test, respectively. Using the Kruskal-Wallis test, residents showed a significant improvement in test scores following the didactic presentation (p = 0.041) while overall results (residents and medical students) also reported a significant difference (p = 0.004). Conclusions. Our results demonstrated that educating family medicine residents and medical students on preoperative evaluation showed significant, quantifiable gains in knowledge following a brief didactic presentation. Given the current gap between guidelines and practice, our results emphasize the need for a formal medical school and residency-based curriculum related to preoperative patient evaluation.